Eminent Identification And Segmentation Of Optic Disk In Digital Fundus Images Using Marr- Hildreth Operator (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes a novel method for the detection of Optic Disk (OD) using fundus image to diagnose glaucoma. Glaucoma is a terrible disease associated with human eyes. As it is a symptomless tragedy that can lead permanent vision loss if not treated in the early stage. Hence, it became the most important research topic in medical field. It is the second leading cause of blindness in the world and it has no cure. Glaucoma has different types, they are normal tension, open angle, close angle etc. Normal tension affects the vision field and damage the optic nerve as well. The term angle means distance between iris and cornea. If the distance is large then it is referred as open angle glaucoma. Similarly if the distance between iris and cornea is short, that is referred as close angle glaucoma. Close angle glaucoma is very painful and it reduces the vision field of eye very quickly. Currently there are treatments are available to prevent vision loss but the disease must be detected in the early stage. Since, OD is the main factor in detection of several eye disease. Glaucoma affects the optic nerve and leads to cupping of optic cup and disk. This paper provides a structure to develop an automatic detection method of OD in retinal images and the methodologies used are optic disc localization and segmentation using Marr-Hildreth operator and Polar Transform.